Copper deposit development potential on the Qinghai-Xizang Plateau in China based on the pressure-state-response framework - Chonghao Liu; Jinshan Xu; Jianan Zhao; Jian Dong; Xiangying Jia; Jing Liu; Xiu Wang (Scientific Reports)
Abstract The Qinghai-Xizang Plateau (QXP) in China is a geological treasure trove known for its complex structures and rich mineral resources. Among these, copper stands out as a critical metal for economic development. However, the exploitation of these resources is not without challenges, particularly in balancing the need for economic growth with the preservation of the plateau’s delicate ecosystem. In this study, we take into account the intricate interplay between human activities, environmental conditions, and economic strategies. By applying a pressure-state-response (PSR) framework and innovatively establishing a comprehensive potential evaluation index, we are able to quantify the development potential of copper deposits on the QXP and to identify key factors influencing the development potential. The results indicate a varied landscape of copper deposit development potential across the QXP. The state layer in the PSR model represents the most significant obstacle to the development potential of copper resources on the QXP. Certain areas, specifically central Xizang, eastern Xizang, and northwestern Yunnan, show high development potential for copper deposits due to favorable geological conditions and policy environments, and strong infrastructure.